PENYULUHAN KESEHATAN DAN PEMERIKSAAN TUMBUH KEMBANG BAYI DAN BALITA DI RW 2 KELURAHAN TANJUNG UMA - Rachmawaty M. Noer; Rizki Sari Utami Muchtar; Mira Agusthia (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The implementation of community service activities aims to increase the understanding and knowledge of mothers who have babies and toddlers about Growth and Development of Infants and Toddlers so that mothers are expected to be able to recognize early signs of disturbance in the growth and development of infants and toddlers. Community service methods used are lectures, discussions and questions and answers as well as a direct examination that includes measurements of height and weight. The material provided includes Nutrition in Infants and Toddlers, the Importance of Immunization for Infants and Toddlers and Signs of Growth and Developmental Disorders of Infants and Toddlers. The results obtained in this activity were all participants stated that this activity was very useful because it increased their horizons and could recognize signs of growth and development problems in their children.